2018
DOI: 10.1016/j.ecoenv.2018.07.066
|View full text |Cite
|
Sign up to set email alerts
|

Di (2-ethylhexyl) phthalate-induced reproductive toxicity involved in dna damage-dependent oocyte apoptosis and oxidative stress in Caenorhabditis elegans

Abstract: Di-(2-ethylhexyl) phthalate (DEHP) is a widely used plasticizer with a high environmental exposure level. As a persistent organic pollutant, DEHP causes reproductive and developmental toxicity in mammals. In this paper, the reproductive toxicity of DEHP was discussed using the model organism Caenorhabditis elegans to determine the sensitivity indices for evaluating the ecotoxicological effects of DEHP. L4 C. elegans larvae to evaluate the LC50 of DEHP and the changes in brood size and generation time, we found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(12 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Moreover, the exposure to DEHP at environmentally relevant doses affected oocyte growth, maturation and ovulation in females of Danio rerio [ 122 ]. In Caenorhabditis elegans , the exposure to DEHP at 10 mg/L decreased the number of oocytes and induced DNA damage in oocytes [ 123 ]. In vitro experiments showed that oocytes from DEHP-exposed female mice at 20 and 40 μg/kg/day induced defects in oocyte meiosis [ 124 ].…”
Section: Phthalates’ Action On Female Reproductive Healthmentioning
confidence: 99%
“…Moreover, the exposure to DEHP at environmentally relevant doses affected oocyte growth, maturation and ovulation in females of Danio rerio [ 122 ]. In Caenorhabditis elegans , the exposure to DEHP at 10 mg/L decreased the number of oocytes and induced DNA damage in oocytes [ 123 ]. In vitro experiments showed that oocytes from DEHP-exposed female mice at 20 and 40 μg/kg/day induced defects in oocyte meiosis [ 124 ].…”
Section: Phthalates’ Action On Female Reproductive Healthmentioning
confidence: 99%
“…Oxidative stress has been described as the disturbances in the redox homeostasis resulting from increased reactive oxygen species (ROS) production or attenuated antioxidant defense systems [1, 2]. Oxidative stress usually leads to damage as free radicals can interact with cell components such as DNA, lipid, and protein [3, 4]. As a common denominator of toxicity, oxidative stress can be induced almost by all types of toxicants.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that this plasticizer interferes with the endocrine system and causes various diseases including reproductive disease, type II diabetes, altered insulin homeostasis, and increases the risk of obesity in both human and animals . DEHP was found hepatotoxic, it induces adverse liver lesions with subsequent development of hepatocarcinoma . Microscopic observations have shown that DEHP exposure causes hypertrophy of liver parenchymal cells, leading to a hepatomegaly, decrease in glycogen stores, and accumulation of lipofuscin granules .…”
Section: Introductionmentioning
confidence: 99%